Bio-Inspired Multimodal Imaging in Reduced Visibility - Lapray, Pierre-Jean; Thomas, Jean-Baptiste; Farup, Ivar (Frontiers in Computer Science, 2022)
The visual systems found in nature rely on capturing light under different modalities, in terms of spectral sensitivities and polarization sensitivities. Numerous imaging techniques are inspired by this variety, among which, the most famous is colour imaging inspired by the trichromacy theory of the human visual system. We investigate the spectral and polarimetric properties of biological imaging systems that willlead to the best performance on scene imaging through haze, i.e., dehazing. We design a benchmark experiment based on modalities inspired by several visual systems, and adapt state-of-the-art image reconstruction algorithms to those modalities.